Nexus of Personality Traits and Peace-Loving Behavior: A Statistical Study of Pre-Service Teacher Learning Outcomes - Abuan, Maricris I.; Discipulo, Amielyn; Semblante, Hermicila C.; Oclarit, Jocelyn C. (RIRAI Publisher, 2026)
In today’s classrooms, teachers must be equipped not only with knowledge but also with the interpersonal traits needed to build respectful, inclusive, and harmonious learning environments. This study investigated how specific personality traits relate to peace-loving behavior among 83 pre-service teachers enrolled in the Bachelor of Elementary Education (BEED) and Bachelor of Secondary Education (BSED) programs. Using a descriptive-correlational design, the study analyzed secondary data from the Manchester Personality Test provided by the guidance office. Statistical tools were used determine the relationships between the traits of agreeableness, extraversion, and resilience, and indicators of peace-loving behavior such as communicativeness, empathy, rule-consciousness, openness to change, and conscientiousness. Results showed that agreeableness had the strongest positive correlation (r = 0.668) with peace-loving behavior, followed by extraversion with a moderate correlation (r = 0.474), and resilience with a weak correlation (r = 0.205). Regression analysis confirmed that all three traits significantly predicted peace-oriented behaviors (p < 0.05). Results also showed how teacher education program activities such as reflecting students experience of peace practices in school can moderate these relationships, potentially enhancing the impact of personality traits on peace-loving behaviors. The study concluded that understanding the link between personality traits and peace-loving behaviors could inform the design of targeted interventions in teacher education programs. Drawing on these insights, TEP instructors could better prepare pre-service teachers to cultivate peaceful classroom environments, ultimately contributing to a more harmonious society.